The geography of Oxia Planum. Issue 2 (1st December 2021) - Fawdon, Peter; Grindrod, Peter; Orgel, Csilla; Sefton-Nash, Elliot; Adeli, Solmaz; Balme, Matt; Cremonese, Gabriele; Davis, Joel; Frigeri, Alessandro; Hauber, Ernst; Le Deit, Laetitia; Loizeau, Damien; et al.
ABSTRACT: We present the geography of Oxia Planum, the landing site for the ExoMars 2022 mission. This map provides the planetary science community with a framework to understand this, until recently, unexplored area. The map comprises (1) a mosaic of the panchromatic Context Camera (CTX) Digital Elevation Models (DEM) and Ortho Rectified Images (ORI) controlled to the High Resolution Stereo Camera (HRSC) multiorbit Digital Elevation Models (DEM) and (2) a mosaic of Colour and Stereo Surface Imaging System (CaSSIS) synthetic colour data products, registered to the CTX ORI mosaic. We define a grid of exploration quadrangles (quads) and an informal group of geographic regions to describe Oxia Planum. These regions bridge the scale gap between features observed on large areas (∼100s km 2 ) and the local geography (10s km 2 ) relevant to the Rosalind Franklin rover's operations in Oxia Planum.